Does the operating temperature of accelerometers affect data measurement during static and dynamic conditions in sports? A randomized-control trial - Gómez-Carmona, C. D.; Rojas-Valverde, D.; Ibáñez, S. J.; Pino-Ortega, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
This study aimed to analyse the effect of two operating temperatures (optimal vs environmental) on IMU internal temperature and accelerometry-based data in two conditions of measurement: (a) static, no movement; and (b) dynamic, a U`16 game-based training soccer session with 14 players. Each session took a 60-min duration and followed an ecological design (no intervention in environmental conditions). Fifty-six WIMU PROTM inertial devices were randomly grouped in four conditions (two operating temperatures × two measurement conditions, 14 devices in each group) and recorded IMUs` internal temperature, resultant acceleration vector and PlayerLoad (PLRT). Devices were placed in the manufacturer`s docking station at the static condition and in a specific harness at the interscapular level at the dynamic condition. Repeated measures t-tests were employed for between-group comparisons at 1-min average sections throughout the register. Between-group differences were found in the static and dynamic conditions in IMUs internal temperature (static: 0-31 min; dynamic: 0-20 min) and resultant acceleration vector (static: 0-29 min; dynamic: 0-19 min). Instead, no differences were found in PLRT dynamics and accumulated PLRT although values in the environmental group were overestimated. In conclusion, WIMU PROTM devices must achieve the optimal operating temperature (38-39°) to avoid measurement error, regardless of the application (short or long sessions).